On Estimates of the Kolmogorov Widths of the Classes $B_{p,θ}^r$ in the Space $L_q$ - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain an order estimate for the Kolmogorov width of the Besov classes $B_{p,{θ }}^r$ of periodic functions of many variables in the space $L_q$ for $2 < p < q < ∞$, which complements the result obtained earlier by the author.